Early Outcome of Surgery in Pediatric Head Injury: Experience From a Tertiary Care Center in Eastern Nepal - Khanal, Babita; Kafle, Prakash; Singh, Sandip K; Yadav, Sunil K; Neupane, Bishomber; Shakya, Ipsa; Yadav, Dipak K (Journal of Institute of Medicine Nepal, 2020)
Introduction Head injuries among the pediatric age group remain an unwelcomed source of morbidity and mortality resulting from falls, motor vehicle accidents, assaults, and child abuse. Early identification and management of traumatic brain injury (TBI) are crucial in halting the progress of the primary insult and preventing or reducing secondary brain injury. The present study aims to investigate the major cause of pediatric TBI and analyze the early outcome and serve as a reference study from a tertiary care center in eastern Nepal.MethodsThis is a prospective cohort study conducted in the Department of Pediatric Medicine and Neurosurgery from February 2018 to January 2020. All the pediatric head injury cases that were managed surgically in the center were included in the study. Presenting Glasgow coma scale (GCS) was correlated with the Glasgow outcome scale (GOS).ResultsThe study population comprised of 65 patients fulfilling the study inclusion criteria. The mean age of the study population was 10.86±4.72 years, fall was the commonest mode of injury (52.3%), 50.8% had mild TBI, 43.1% had moderate TBI and 6.2% had severe TBI. Depressed skull fracture with underlying extradural hematoma (EDH) or contusion was the commonest pathological diagnosis seen in 30.8 % (20) cases. The mean duration of hospital stay was 2.6 days. The presenting GCS correlated well with the outcome.ConclusionThis study concluded that the timely management of pediatric TBI can prevent grave prognosis and the patients presenting GCS and the pupillary reaction has strong correlation with the outcome.